Упростите выражение : а) 5a/12+a/12, б) 14b²/5-9b²/5, в) ax/x+y +ay/x+y, г) a/a-1 - 1/a-1, д) 4a+1/ 3a-3 - a+1 / 3a - 3, е) 3a + 2b / a+b + 2a + 3b/ a+b.
А) 5a/12+a/12=6а/12=а/2 б) 14b²/5-9b²/5=5b²/5=b² в) ax/x+y +ay/x+y=(ax+ay)/(x+y)=a(x+y)/(x+y)=a г) a/a-1 - 1/a-1=(a-1)/(a-1)=1 д) 4a+1/ 3a-3 - a+1 / 3a - 3=(4a+1-a+1)/(3a-3)=(3a+2)/(3a-3) е) 3a + 2b / a+b + 2a + 3b/ a+b=(3a+2b+2a+3b)/(a+b)=(5a+5b)/(a+b)=5(a+b)/(a+b)=5
Спасибо
А)6а/12 = а/2 б) 5б²/5=б² в) ахy/x+y г) а-1/а-1=1 д)3а+2/3а-3 е) 5а+5б/а+б